Case report: use of pleural dialysis as an alternate means of renal replacement therapy in three cats - Vernier, Mara E.; Fick, Meghan E.; Johnson, Tyler E.; Ueda, Yu; Vigani, Alessio (Frontiers in Veterinary Science, 2024)
ObjectiveThe objective of this case series is to describe the indications, methodology, and short-term outcomes of three cats with severe azotemia managed with pleural dialysis.Case summaryThree cats were presented separately to the emergency room (ER) on referral for severe azotemia of varying etiologies. Despite aggressive medical and/or surgical management, none of the cats showed improvement in their blood urea nitrogen (BUN) or creatinine values. Renal replacement therapy was recommended, but for varying reasons, the patients were unable to undergo a traditional extracorporeal method, such as intermittent hemodialysis (IDH). Instead, pleural dialysis was performed, and all three cats showed improvement in their renal values during and after their treatment. No significant complications were documented as a result of pleural dialysis. Two of the three cats were discharged from the hospital and the third cat was humanely euthanized due to poor prognosis.New or unique information providedPleural dialysis is a novel therapeutic procedure that is not documented in veterinary or human literature. This method of renal replacement therapy was well-tolerated and had no reported complications. Careful case selection and risk-benefit analysis should be considered before attempting this procedure. Further studies are necessary to further define the utility of this therapeutic intervention, evaluate the incidence of complications, and determine long term outcomes following the procedure.